Species and Densitiy of Crabs in Mangrove Ecosystem Apar Village, North Pariaman District, Pariaman, West Sumatera - Nada Fitria; Nur El Fajri; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCrab is potential mangrove fishery that have important economic value. Apar village has broad mangrove an area of 8 ha, this mangrove has been degraded due to illegal logging and the clearing of mangrove ecosystem. The impact due to reduced and damaged mangrove ecosystem is a decrease in aquatic productivity and indirectly affects the conditions of biota that live in the mangrove ecosystem Apar village, a research was conducted on july 2019. The sample observations used a purposive sampling method and were divided into 2 stations with different mangrove conditions. Result shown that there were 5 crabs species present Uca dussmieri, Uca rosea, Perisesarma bidens, Perisesarma sp., and Parathelphusa convexa. the crabs density value was ranged from 2 to 3,533 ind/m2 and the mangrove density was ranged from 633 to 1866 p/ha. Results of correlations the mangrove density with density of crabs is Y = 0,000x + 0,607 and coefficient of determination (R2) 0,290. A coefficient of correlation is 0,54, which mean there is a positive correlation between the mangrove with density of crabs. Keywords: density, crabs, , mangrove, apar village